Asteromys punctus Ameghino (Rodentia, Hystricognathi, Cavioidea) from the late Oligocene of Patagonia (Argentina) and the early evolution of Cavioidea sense strict - Pérez, María Encarnación (2012)
Asteromys punctus Ameghino was only known from the holotype, found in the Deseadan locality Cabeza Blanca (Chubut Province, Argentina). This species was included in the Family “Eocardiidae” because of its high-crowned cheek teeth and reduction of the mesoflexid-mesofossettid. In turn, “Eocardiidae”, together with Caviidae and Hydrochoeridae, has been regarded as part of Cavioidea sensu stricto, a large group of rodents characterized by double heart-shaped occlusal surface, moderate hystricognathy, and short extension of the lower incisors. The aim of this work is to report a new specimen of Asteromys punctus found in the Deseadan locality Laguna de Los Machos, Chubut Province, and to discuss the affinities of this taxon within Cavioidea s.s. in the context of a recently published phylogenetic analysis. In that analysis, four unambiguous synapomorphies support the inclusion of A. punctus within this clade: presence of mandibular foramen below the m3, root of the lower incisors extending up to the level of the posterior lobe of m2, lateral crest dorsally convex and deflecting anteroventrally from the base of the coronoid process, and horizontal crest as a low and broad ridge. Furthermore, the information provided by the holotype and the new material within a phylogenetic framework allows a discussion of the evidence that supports this taxon as the basalmost member of Cavioidea s.s., placing Asteromys in a critical position for understanding the early evolutionary history of Cavioidea s.s..